The Relationship between Service Quality and Loyalty of the Leasing Company in Muang District, Suratthani Province - กาสาเอก, จิตรา; ล่องประเสริฐ, สุณีย์; สุขศรี, นิตย์ หทัยวสีวงศ์ (Journal of Management Sciences Suratthani Rajabhat University, 2016)
The objectives of this research were to study the service quality, loyalty and the relationship between service quality and loyalty. The data were collected by questionnaires which had Cronbach’s reliability of 0.85 and 0.80 from the 400 users of a leasing company in Muang District, Surat Thani province. Analyzing the data frequency, standard deviation, and Spearman rank correlation coefficient found that the service users commented on the service quality for the highest 7 aspects consisting of process, physical, place, promotion, price, people and product. The service users commented on the loyalty for the highest 4 aspects consisting of users’ word of mouth, repeat service, security products and services and feeling. The service quality was related in the positive direction for the lowest 7 aspects which consisted of people, promotion, physical, process, price, product and place.